Compensated activation of coagulation in patients with abdominal aortic aneurysm: effects of heparin treatment prior to elective surgery - Jelenska, Maria Magdalena; Szmidt, Jacek; Bojakowski, Krzystof; Grzela, Tomasz; Palester-Chlebowczyk, Magorzata (Thrombosis and Haemostasis, 2004)
Elective surgery of abdominal aortic aneurysm (AAA) sometimes leads to excessive bleeding and disseminated intravascular coagulation (DIC), even in patients with normal preoperative coagulation parameters. Coagulation screen, performed routinely before surgery is of limited value in the assessment of compensated activation of the haemostatic system. In this study, we used a number of additional tests (D-dimer, prothrombin fragment 1+2, antithrombin, and activation of fibrinolysis in the platelet poor plasma) for the diagnosis of compensated activation of the haemostatic system in AAA-patients. Ddimer and marker of thrombin generation (prothrombin fragment 1+2) positively correlated with each other (r = 0.768, P < 0.001). Out of 71 AAA patients, 15 patients had normal global coagulation times, but those with a Ddimer concentration above 3000 ng/ml were selected for preoperative low molecular weight heparin (LMWH) treatment. Administration of LMWH diminished coagulation abnormalities (D-dimer and prothrombin fragment 1+2 decreased significantly) and resulted in the increase of platelet number and fibrinogen concentration, indicating their previous consumption. Despite differences in aneurysm diameters between the groups of 15 LMWH treated patients (mean 70.9 ± 16 mm) and the reference group of 20 untreated AAA patients (mean 52.3 ± 8.0 mm), intraoperative parameters (operation time, blood loss and transfusion demands) were similar.
Keywords: Abdominal aorta aneurysm; compensated activation of coagulation; low molecular weight heparin treatment